Possibility of solar thermal power generation technologies in Nigeria: Challenges and policy directions. (June 2019) - Akinyele, Daniel; Babatunde, Olubayo; Monyei, Chukwuka; Olatomiwa, Lanre; Okediji, Adebunmi; Ighravwe, Desmond; Abiodun, Onile; Onasanya, Mobolaji; Temikotan, Kehinde
Highlights: The study discussed the possibility of solar thermal power system in Nigeria. Barriers to uptake and application of solar thermal power in Nigeria are presented. A policy framework is presented for solar thermal issues in Nigeria. Abstract : This paper presents a brief overview of solar thermal power generation technologies (parabolic trough, central tower receiver, linear Fresnel reflecting and parabolic dish concentrators) and their possible application in Nigeria. It further discusses an array of barriers to the development of the technologies, such as the lack of understanding of solar thermal systems, lack of incentives for renewable technologies and previous experience of solar photovoltaic systems failure that is making people doubt the viability of renewable electricity. Other barriers that were considered are lack of technical expertise, high technology cost and lack of project funding, including a lack of enabling policies to drive the technologies. This study then develops a policy framework that will help to understand and address some of the identified challenges to achieve widespread adoption, application, and diffusion in Nigeria. In addition, the framework will provide useful insights into the major issues that affect community-based or regional solar thermal power systems in developing countries. Widespread application of these clean energy technologies can help mitigate climate change.